2020
DOI: 10.1021/acssuschemeng.0c06675
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Voltammetric Detection of Melatonin in Pharmaceutical Products by Highly Conductive Porous Graphene-Gold Composites

Abstract: This work presents a novel melatonin sensor based on unfunctionalized macroporous graphene networks decorated with gold nanoparticles for the differential pulse voltammetric detection of melatonin in pharmaceutical products. Highly porous graphene structures were prepared by metallic template-assisted chemical vapor deposition, and their active surface area and electrocatalytic activity were improved by electrochemical deposition of gold nanoparticles (50−250 nm) on their struts. The graphene-gold electrodes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…25 Ruoff et al 31 have reported that during microwave irradiation at 1100 W for 40 s, overlapped and crumpled RGO sheets are formed. Similar to CVD-grown GFs, 1,32 vertically standing graphene nanoflakes with sharp edges are observed (Figure 1e). It is noteworthy that thermal annealing at 800 °C for 4 h does not significantly change the interlinked structure of the TrGO (TA-GF) (Figure 1d,h).…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…25 Ruoff et al 31 have reported that during microwave irradiation at 1100 W for 40 s, overlapped and crumpled RGO sheets are formed. Similar to CVD-grown GFs, 1,32 vertically standing graphene nanoflakes with sharp edges are observed (Figure 1e). It is noteworthy that thermal annealing at 800 °C for 4 h does not significantly change the interlinked structure of the TrGO (TA-GF) (Figure 1d,h).…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…Based on eqn (1), the electroactive surface area of AuNPs@Gr (0.49 cm 2 ) was found to be increased by 48.5% compared to Gr (0.33 cm 2 ), which was similar to the results of previous studies. 20 The results suggested that the improvement in the detection of DA, 5-HT, and MEL was the consequence of the increment in the catalytically active sites of the AuNPs@Gr electrode.…”
Section: Resultsmentioning
confidence: 95%
“…† Among them, the coarser particles are mainly formed in high-energy regions, such as edges or wrinkles of the graphene sheets, which have higher driving forces to promote the formation of gold nanoparticles. 20 EDS tests were performed to evaluate the detailed elemental composition of the modified electrode. The distribution of carbon and gold within the modified electrode can be observed in element mapping images (see Fig.…”
Section: Characterization Of Aunps@grmentioning
confidence: 99%
See 1 more Smart Citation
“…The affordable cost and eco-friendly preparation of the SNGCE material support its investigation as a sensing element in the development of an electrochemical sensor for melatonin. The tailoring and design of the proposed electrochemical sensor was achieved by exploring the well-known properties of gold nanoparticles for electrochemical sensing applications [ 30 , 31 ]. The prepared sensing materials were further investigated in terms of their electrochemical and electroanalytical properties and performance toward melatonin determination.…”
Section: Introductionmentioning
confidence: 99%